2000
DOI: 10.1002/clc.4960230404
|View full text |Cite
|
Sign up to set email alerts
|

Current status of stress echocardiography

Abstract: Summary: Stress echocardiography is a widely applied technique for the evaluation of individuals with known or suspected coronary artery disease. The technique combines echocardiographic imaging with exercise testing or phannacologic stress. Advances in digital image acquisition and harmonic imaging have substantially improved the quality of echocardiographic images, and have therefore increased general applicability of stress echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Using dobutamine stress echocardiography testing rather than exercise stress testing in pediatric patients with a history of KD [10], and in comparison with coronary angiography, the sensitivity was 19/21 or 90%, while the specificity was 100%. A recent review [11]suggested that exercise stress testing in adults with known or suspected coronary disease yielded sensitivities of 74–97%, with a pooled average of 85%. In the same article, the specificity varied from 64 to 100%, with a pooled average of 77%.…”
Section: Discussionmentioning
confidence: 99%
“…Using dobutamine stress echocardiography testing rather than exercise stress testing in pediatric patients with a history of KD [10], and in comparison with coronary angiography, the sensitivity was 19/21 or 90%, while the specificity was 100%. A recent review [11]suggested that exercise stress testing in adults with known or suspected coronary disease yielded sensitivities of 74–97%, with a pooled average of 85%. In the same article, the specificity varied from 64 to 100%, with a pooled average of 77%.…”
Section: Discussionmentioning
confidence: 99%